LINE×TESTER ANALYSIS OF THE SECOND GENERATION OF MAIZE GENOTYPES IN SULAIMANI AGROCLIMATIC CONDITIONS, IRAQ - Lanja M. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Eight inbred lines of maize (Zea mays L.) and their 16 F2 hybrids were used in this investigation during the spring season 2023, utilizing the line × tester mating design. This study was conducted at two environmentally different locations at Sulaimani: Dukan and Qlyasan. The hybridization consisted of four inbred lines (NADH905, NADH102, NA106, and SaraNA) which were used as lines with four inbred lines (NA225, NAHD503, ZN12, and NAPI 5012) which were used as testers. The cross SaraNA×NAPI5012 and NADH 905×NA225 recorded the highest values for kernel yield at Dukan and Qlyasan locations respectively. The maximum heterosis values concerning kernel yield were obtained by the crosses SaraNA×NAPI5012 and NA106×NAPI5012 at Dukan and Qlyasan respectively. The maximum positive GCA effects for kernel yield were recorded by parents SaraNA and ZN12 at Dukan and parents NA106 and NA225 at Qlyasan locations. SCA effect for the crosses concerning kernel yield showed that the crosses SaraNA×NAPI5012 and NADH 905×ZN12 obtained the maximum positive SCA values at Dukan and Qlyasan locations respectively.